Ter tempo para aprender música: experiências vividas e compartilhadas por aposentados - Mata, Hosana Rodrigues Ferreira da (2014)
This dissertation focuses on retirement as a moment of musical learning. This work has as main objective to understand the retirement as a moment of life to seek to learn music, and as specific objectives intend to understand how the musical experiences are lived and shared with/by these retired people in areas of teaching/learning, collective or not, as in the cases of choir practice, or learning an instrument, individually or collectively. In a qualitative approach, the research method adopted was the case study, using such procedures for data collection interview. The music education as a social practice (SOUZA, 2004), the thought of retirement associated to leisure (DUMAZEDIER, 1994, 1999), and leisure associate to the potential of education in retirement (MARCELLINO, 1987, 1995, 2000, 2002, 2007) were the theoretical basis for the reflection on all the collected material from the interviews. The final considerations of this research are associated with the process on which people that retire experience, the way that musical learning becomes important in their lives, and also how these people experience music in their lives and share in spaces of teaching / learning collective or individual.